Pre-project research cycle of the architectural environment of the small town’s historical center as an analytical stage of it reconstruction - Leshchenko, Nellya (КНУБА, 2016)
To create a competent reconstruction projects in the historical environment it’s necessary to carry out pre-project research cycle. It’s goal - to produce detailed baseline data. Pre-project research should be carried out using the method of graph-analytical analysis of the historical architectural environment and its current state, the method of comparative analysis, synthesis by drawing up the result recommendations schemes. The article marks the stages of pre-project research of the architectural environment of the small town's historic center. It consists of historical-genetic analysis, analysis of the current state of the urban historical architectural environment, implementation the historical-reference plan, project of zones of protection monuments of architecture and urban planning, preparation the historical and urban planning substantiation. These researches are directed to identify characteristics of the formation and development of historic urban environment, to determine its value and the state of preservation, to define the limits of architectural and townplanning constraints and demands during reconstruction or new construction in the historic environment. The article shows the sequence of pre-project researches and their mutual influence. The result schemes of each stage were noted. A scheme-model of reconstruction activities as the result pre-project research and as the implementation of recommendation to the reconstruction project was determined.
Keywords: pre-project research cycle; historical-genetic analysis; historical-reference plan; the historical and urban planning substantiation.